THE REGIONAL DEVELOPMENT IN ROMANIA`S RURAL AREAS - SUPPORTING PROGRAMMES AND ACTUAL ISSUES - Silviu, Beciu; Nistor, Stefania; Popa Oana, Ecaterina; Olteanu, Victor (Economics of Agriculture, 2011)
Situated among the last countries that joined the European Union, Romania is one of The European Union countries with the biggest problems in terms of socio-economic development at regional and national level. The Romanian accession in the EU brought the need for reconstituting the regions. Thus were created eight regions and even if they are not administrative-territorial units, and havent legal personality, they serve to coordinate regional development and to facilitate access to EU regional development funds.This article aims to present the recent regional developments in Romania in terms of: regional integration and the tendency in reducing regional disparities, especially in the rural areas; the ways in which the EU funds have been accessed at the regional level; which are the current issues and diffculties. Method used has involved the analysis of statistical data and feld study in the rural areas of the regions of development.